Ethnographic Things: Objects and Subjects in Haida History - St. George, Robert (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2012)
The social history and aesthetic value of art made by Haida people are subjects often in conflict or marked by a lack of clarity.  This essay attempts to explore the things made on Haida Gwaii for different purposes: for entirely local use and in relation to one or two mythic cycles. Then, beginning in the mid-nineteenth century, the collectors, dealers, and museum of the western world arrived; they took thousands of objects away, and by 1880 many Haida artists could assert continuity by making model houses, totem poles, and boats for growing souvenir markets.